Gobernanza de las aguas transfronterizas: Fragilidades institucionales en AmÉrica del sur - Mello Sant’Anna, Fernanda [UNESP]; Villar, Pilar Carolina (Ediciones Universidad de Salamanca, 2015)
Since the 1990s, the concept of governance rose to prominence in the literature regarding transboundary waters, as well as the international cooperation among riparian States. This article seeks to determine the fragilities in the governance of the major transboundary water resources in South America: the Amazon and La Plata River Basins. In spite of the current international agreements, including those regarding infrastructure development and supranational organizations, water governance presents fragilities related to institutional problems, lack of social participation and difficulties in structuring a common project of development.
Transboundary water resources governance: Institutional fragilities in South America
Keywords: Amazon River Basin; International cooperation; La Plata River Basin; Transboundary water resources; Water governance